Enhanced clinical photoacoustic vascular imaging through a skin localization network and adaptive weighting - Chuqin Huang; Emily Zheng; Wenhan Zheng; Huijuan Zhang; Yanda Cheng; Xiaoyu Zhang; Varun Shijo; Robert W. Bing; Isabel Komornicki; Linda M. Harris; Ermelinda Bonaccio; Kazuaki Takabe; et al. (Photoacoustics)
Photoacoustic tomography (PAT) is an emerging imaging modality with widespread applications in both preclinical and clinical studies. Despite its promising capabilities to provide high-resolution images, the visualization of vessels might be hampered by skin signals and attenuation in tissues. In this study, we have introduced a framework to retrieve deep vessels. It combines a deep learning network to segment skin layers and an adaptive weighting algorithm to compensate for attenuation. Evaluation of enhancement using vessel occupancy metrics and signal-to-noise ratio (SNR) demonstrates that the proposed method significantly recovers deep vessels across various body positions and skin tones. These findings indicate the method’s potential to enhance quantitative analysis in preclinical and clinical photoacoustic research.